2016
DOI: 10.1007/s11746-016-2822-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Classification of Extra Virgin Olive Oil from Five Less Well‐Known Greek Olive Cultivars

Abstract: The present study comprises the second part of an ongoing study focusing on olive oil from five less well‐known Greek cultivars for three of which there are no data available in the literature regarding their chemical composition. A total of 74 olive oil samples were collected during the harvesting periods 2012–2013 and 2013–2014. Headspace‐solid phase microextraction was applied to determine the olive oil volatile profile. Fifty‐six compounds were identified and semi‐quantified by CG–MS. Furthermore, fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 34 publications
3
39
1
Order By: Relevance
“…These researchers determined the volatile composition of olive oil samples from two Turkish cultivars (Ayvalik and Memecik) and reported difficulty in combining volatiles with color, acidity and PV for differentiation purposes. On the other hand, the results of the present study are in agreement with those reported by Kosma et al [47], according to which the combination of analytical parameters, i.e., VC and color, increased the classification rate for various olive cultivars.…”
Section: Geographical Differentiation Based On the Combination Of Vc supporting
confidence: 94%
“…These researchers determined the volatile composition of olive oil samples from two Turkish cultivars (Ayvalik and Memecik) and reported difficulty in combining volatiles with color, acidity and PV for differentiation purposes. On the other hand, the results of the present study are in agreement with those reported by Kosma et al [47], according to which the combination of analytical parameters, i.e., VC and color, increased the classification rate for various olive cultivars.…”
Section: Geographical Differentiation Based On the Combination Of Vc supporting
confidence: 94%
“…The small differences among certain FA in the standards are due to the natural variations that are unrelated to the authenticity of olive oil. Indeed, research studies have confirmed genetic and environmental factors such as olive variety (Kosma et al, , b), geographical origin (Borges et al, ), and climate and soil quality (Salomone and Ioppolo, ); growing conditions such as harvest timing (Dag et al, ) and irrigation strategies (Gómez‐Rico et al, ) can affect the values of FA and/or sterols, potentially leading an authentic olive oil failing to meet the standards.…”
Section: Introductionmentioning
confidence: 93%
“…To our knowledge no dedicated literature exists for the fatty acid composition of the above discussed PDO products. [50] The composition of fatty acids or their triacylglycerols has been used to characterize origin of Greek VOOs [38,[50][51][52][53] but no study exists to support differentiation among Greek PDOs or PGIs using different chemometric approaches though such a need has been foreseen early enough. Available literature mostly regards VOOs of Koroneiki cultivar.…”
Section: Fatty Acids and Triacylglycerol Compositionmentioning
confidence: 99%